The relationship and mechanism of screen time and academic performance among adolescents: an empirical study based on CEPS - Feng, Xiaosu; Ren, Shuanquan; Shi, Peng (Frontiers in Public Health, 2025)
ObjectiveThere is an association between adolescents’ screen time and academic performance, but the conclusions remain controversial. In particular, there is a lack of research on Chinese students who face higher academic pressure. Based on this, we aim to explore the relationship and mechanisms between screen time and academic performance among Chinese adolescents.Methods17,150 junior middle school students from China Education Panel Survey (CEPS) from 2013 to 2014 were selected as the participants of the survey. Multiple linear regression analysis was used to explore the relationship between screen time and adolescents’ academic performance. On this basis, the Z-test of regression coefficient is used to further investigate whether there is heterogeneity in the type of screen exposure in this relationship. The possible mediating mechanism of the relationship between screen time and adolescents’ academic performance was investigated through path analysis.ResultsScreen time and Chinese (β = −0.022), mathematics (β = −0.048), English (β = −0.043) and 3 total scores (β = −0.113), there was a significant negative correlation (p < 0.01). The time spent watching TV and the time spent on the Internet and playing games were significantly negatively correlated with the academic performance of adolescents (p < 0.01), but there was heterogeneity in the type of screen exposure. The time spent on the Internet and playing games had a significant impact on adolescent mathematics (β = −0.063), English (β = −0.047) and total scores (β = −0.148) produced more negative effects. Path analysis found that cognitive performance was the main path of the relationship between the two, sleep time, mental health, classmate relationship and parent–child relationship were important distal paths, and social relationship construction played a stronger intermediary role in the relationship between screen time and adolescent academic performance.ConclusionThe results support the “negative impact” hypothesis, and the negative effect of surfing the Internet and playing games on adolescents’ academic performance is greater. Screen time directly or indirectly affects academic performance by increasing sleep time, mental health, classmate relationship and parent–child relationship, but the mediating effect of BMI and subjective health perception has not been verified.